AKTIVITAS USAHATANI BAWANG DAUN DAN KENTANG DI DESA BONGKUDAI SELATAN KECAMATAN MOOAT KABUPATEN BOLAANG MONGONDOW TIMUR - Jennifer C. Rondonuwu; Mex L. Sondakh; Caroline B.D. Pakasi (Universitas Sam Ratulangi, 2019)
ABSTRACT The purpose of this research is to find out how the activities of onion and potato farming in South Bongkudai Village, Mooat District, Bolaang Mongondow Regency East. The purpose of this research is to find out how the activities of onion and potato farming in South Bongkudai Village, Mooat District, Bolaang Mongondow Regency East. The population in this study are all farmers who have worked on potato and onion farming. Samples were taken as many as 30 respondents engaged in onion plants and 30 respondents engaged in potato plants. Simple random sampling (simple random sampling) in the village of South Bongkudai. The data obtained in this study were analyzed by identifying activities using descriptive analysis methods with the help of tables. Based on the results of the study showed that some of the economic activities of the agricultural sector in the village of South Bongkudai consisted of horticultural crops, especially leeks and potatoes. The highest activity in the employment of onion farming is maintenance activities and for potato farming is maintenance activities. At the income level, potato farming is higher than leek farming. Keywords : Activities of farming, labor absorption, income farming